2018
DOI: 10.3389/fnins.2018.00431
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic Acid Prevents Oxidative Stress and Apoptosis by Inhibiting the Translocation of α-Synuclein Into Mitochondria

Abstract: The association of α-synuclein (α-syn) with mitochondria occurs through interaction with mitochondrial complex I. Defects in this protein have been linked to the pathogenesis of Parkinson disease (PD). Overexpression of α-synuclein in cells has been suggested to cause elevations in mitochondrial oxidant radicals and structural and functional abnormalities in mitochondria. Asiatic acid (AA), a triterpenoid, is an antioxidant that is used for depression, and we have shown that pretreatment with AA can prevent PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…Application of oligomeric α-synuclein increases ROS production and lipid peroxidation [ 24 , 25 ]. α-synuclein is translocated to mitochondria and directly interacts with mitochondrial proteins including ATP synthase to lower mitochondrial inner membrane potential, thus altering neuronal energy metabolism and opening mitochondrial death channels [ 24 , 26 ]. Increased oxidative stress induced by treatment with hydrogen peroxide or depletion of antioxidant enzymes enhances post-translational modification and aggregation of α-synuclein and worsens the progression of PD [ 27 , 28 , 29 ].…”
Section: Oxidative Stress and Park Genesmentioning
confidence: 99%
“…Application of oligomeric α-synuclein increases ROS production and lipid peroxidation [ 24 , 25 ]. α-synuclein is translocated to mitochondria and directly interacts with mitochondrial proteins including ATP synthase to lower mitochondrial inner membrane potential, thus altering neuronal energy metabolism and opening mitochondrial death channels [ 24 , 26 ]. Increased oxidative stress induced by treatment with hydrogen peroxide or depletion of antioxidant enzymes enhances post-translational modification and aggregation of α-synuclein and worsens the progression of PD [ 27 , 28 , 29 ].…”
Section: Oxidative Stress and Park Genesmentioning
confidence: 99%
“…In relation to mitochondria, the triterpenoid, asiatic acid, reportedly protects neurons from cell death by preventing mitochondria-dependent apoptosis in a cellular model of AD [297]. Another study also demonstrated that asiatic acid blocked the translocation of α -synuclein into mitochondria, thereby protecting it against oxidative stress and apoptosis [298]. Asiatic acid also prevented the α -synuclein-induced decrease in mitochondrial membrane potential in a Drosophila model of PD [298].…”
Section: Mitochondrial Dysfunction In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Another study also demonstrated that asiatic acid blocked the translocation of α -synuclein into mitochondria, thereby protecting it against oxidative stress and apoptosis [298]. Asiatic acid also prevented the α -synuclein-induced decrease in mitochondrial membrane potential in a Drosophila model of PD [298].…”
Section: Mitochondrial Dysfunction In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Finally, the cells were photographed with a fluorescence microscope (Nikon, Japan) at Ex488 nm/Em535 nm and Ex 540 mm/Em570 nm[34].2.11. In Vivo Mouse Model Experiments.…”
mentioning
confidence: 99%